Environmental Analysis with 2D Transition-Metal Dichalcogenide-Based Field-Effect Transistors - Chen, Xiaoyan; Liu, Chengbin; Mao, Shun (Nano-Micro Letters, 2020)
Field-effect transistors (FETs) present highly sensitive, rapid, and in situ detection capability in chemical and biological analysis. Recently, two-dimensional (2D) transition-metal dichalcogenides (TMDCs) attract significant attention as FET channel due to their unique structures and outstanding properties. With the booming of studies on TMDC FETs, we aim to give a timely review on TMDC-based FET sensors for environmental analysis in different media. First, theoretical basics on TMDC and FET sensor are introduced. Then, recent advances of TMDC FET sensor for pollutant detection in gaseous and aqueous media are, respectively, discussed. At last, future perspectives and challenges in practical application and commercialization are given for TMDC FET sensors. This article provides an overview on TMDC sensors for a wide variety of analytes with an emphasize on the increasing demand of advanced sensing technologies in environmental analysis. Article Highlights: 1 Recent advances of two-dimensional (2D) transition-metal dichalcogenide (TMDC)-based field-effect transistor (FET) sensors for environmental analysis are summarized. 2 Representative TMDC FET sensors in gaseous and aqueous media analysis are introduced. 3 Challenges and future research directions of 2D TMDC FET sensors are discussed.